Education on the Use of Audio Visual Applications for Guardians of Students in Ganting Village Facing Online Schools During the 2020 Pandemic: Edukasi Penggunaan Aplikasi Audio Visual Bagi Wali Murid di Desa Ganting Menghadapi Sekolah Daring Selama Masa Pandemi Tahun 2020 - Aesthetika, Nur Maghfirah; Febriana, Poppy; Destiana, Evie; Mohammad R, Alfaro (Procedia of Social Sciences and Humanities, 2022)
During the Covid-19 pandemic, the education sector experienced a significant impact, which made learning must be done online. This makes people demanded to be able to use technology, especially the parents of kindergarten-elementary students' guardians. Because in order to help work on school assignments given by teachers to students through digital media. In general, teachers on average kindergarten assign assignments at least once per day to students. Then the work is done by making a video of how to work on the assignment and it is done by the student's guardian. So that it is interesting through online media. Ganting Village, is one of the villages that also has a kindergarten school which is directly sheltered by a village government agency. In this condition, it is known that there are still many kindergarten-SD students' parents who are less well off in digital media as a means of running online schools. This situation makes many guardians difficult in facing the Brave school, starting from limited knowledge about technology, the cost of internet quota, which can also have an impact on the impact of interest in learning. The community service program entitled Education on the Use of Audio Visual Applications for Guardian Students in Ganting Facing Village Sekolah Berani Salama during the Pandemic Period aims to provide training to parents of students who currently find it difficult to use social media application technology in completing their child's assignments. The output of this program can be seen with scientific contributions to scientific articles, and video documentation of activities can be displayed via the youtube channel.